Ameloblastic fibro-odontoma in mandibular molar region: A case report. Issue 1 (April 2019) - Otsugu, Masatoshi; Okawa, Rena; Nomura, Ryota; Nakano, Kazuhiko
Abstract: We report a case of ameloblastic fibro-odontoma (AFO) in the mandibular molar region. A Japanese boy aged 6 years 8 months visited the Pediatric Dentistry Clinic of Osaka University Dental Hospital with dental caries as the chief complaint. Radiography revealed a well-defined homogenous mixed radiopaque mass like dentition above the crown of the mandibular left first molar. At the age of 6 years 9 months, enucleation of the tumor mass was performed under local anesthesia. Based on the histological findings, the diagnosis was AFO. Following enucleation, the left first molar showed a tendency for eruption.